Beach and Coastal Survey of Thailand: What Future for Surf Tourism / Steven Andrew Martin and Ilian Assenov - Martin, Steven Andrew; Assenov, Ilian (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
There are surfers on vacation looking for waves. Surfing and surf tourism run parallel: they are focused upon location-specific destinations where natural resources and phenomena occur conducive to the sport; and travelling for the sake of surfing new places is as old as the sport itself. This research serves to improve the overall understanding of surf tourism in Thailand and to offer recommendations for sustainability and quality of experience. As an investigation, three ideas within the broad environment of Thailand have been rationalized: to survey and assess the coastal resource in order to determine the plausibility and practicability of surf tourism in Thailand (including the discovery and documentation of surf breaks); to interpret the surf tourist characteristics of Phuket, Thailand, through unstructured and semi-structured personal interviews; and to answer the question: "What future for surf tourism in Thailand?" This research has idented and assessed five of Thailand's provincial areas most suited for surf tourism, and has identified that contrary to popular belief there are a large number of areas suitablefor surfing and surf tourism, including those for advanced, intermediate, and beginner surfers. In all, 80 surfing areas were surveyed. A refined Thailand-specific definition for surf tourism is suggested, reflecting the natural environment and the characteristics of the current surf tourists. The paper concludes by identiffing the future prospects, challenges, and related issues for sustainable surf tourism in Thailand.